[N,N′-Bis(4-bromobenzylidene)-2,2-dimethylpropane-κ(2) N,N′]iodidocopper(I) - Kia, Reza (International Union of Crystallography, 2009)
The title compound, [CuI(C(19)H(20)Br(2)N(2))], lies across a crystallographic mirror plane. The coordination around the copper centre is distorted trigonal planar, with a bite angle of 94.7 (3)°. A six-membered chelate ring in a chair conformation is formed by the coordination of the imine N atoms of the bidentate ligand to the Cu(I) atom. This conformation is required by the crystallographic mirror symmetry. The interplanar angle between the benzene rings is 74.85 (19)°. The crystal structure exhibits weak intermolecular C—H⋯π interactions, which link the molecules into chains along the b axis.